Association of exposure to mixture of chemicals during pregnancy with cognitive abilities and fine motor function of children - Brennan Kearns, Pavla; van den Dries, Michiel A.; Julvez, Jordi; Kampouri, Mariza; López-Vicente, Mónica; Maitre, Lea; Philippat, Claire; Småstuen Haug, Line; Vafeiadi, Marina; Thomsen, Cathrine; Yang, Tiffany C; Vrijheid, Martine; et al. (Environment international, 2024)
Chemical exposures often occur in mixtures and exposures during pregnancy may lead to adverse effects on the fetal brain, potentially reducing lower cognitive abilities and fine motor function of the child. We investigated the association of motheŕs exposure to a mixture of chemicals during pregnancy (i.e., organochlorine compounds, per- and polyfluoroalkyl substances, phenols, phthalates, organophosphate pesticides) with cognitive abilties and fine motor function in their children. We studied 1097 mother–child pairs from five European cohorts participating in the Human Early Life Exposome study (HELIX). Measurement of 26 biomarkers of exposure to chemicals was performed on urine or blood samples of pregnant women (mean age 31 years). Cognitive abilities and fine motor function were assessed in their children (mean age 8 years) with a battery of computerized tests administered in person (Raveńs Coloured Progressive Matrices, Attention Network Test, N-back Test, Trail Making Test, Finger Tapping Test). We estimated the joint effect of prenatal exposure to chemicals on cognitive abilities and fine motor function using the quantile-based g-computation method, adjusting for sociodemographic characteristics. A quartile increase in all the chemicals in the overall mixture was associated with worse fine motor function, specifically lower scores in the Finger Tapping Test [-8.5 points, 95 % confidence interval (CI) −13.6 to −3.4; −14.5 points, 95 % CI –22.4 to −6.6, and −18.0 points, 95 % CI −28.6 to −7.4) for the second, third and fourth quartile of the overal mixture, respectively, when compared to the first quartile]. Organochlorine compounds, phthalates, and per- and polyfluoroalkyl substances contributed most to this association. We did not find a relationship with cognitive abilities. We conclude that exposure to chemical mixtures during pregnancy may influence neurodevelopment, impacting fine motor function of the offspring.